A Study of Psychological Counselling Needs Among Adolescents - Dr. Rajinder Kour (Kurdish Studies, 2021)
Adolescence represents a critical developmental crossroads where biological maturation encounters a rapidly evolving socio-cultural landscape. This study investigated the level of psychological counselling needs among 200 adolescents in the Kathua district of Jammu and Kashmir, examining the influence of gender, locale, institution type, and family structure. Utilizing a quantitative descriptive survey design and the standardized Psychological Counselling Needs Scale (PCNS), the analysis revealed that 59% of adolescents exhibit "High" or "Above Average" levels of need. Significant differences were observed across gender, locale, and family structure, with adolescent boys, rural residents, and those from nuclear families displaying higher counselling requirements. Conversely, school type (government vs. private) did not emerge as a significant differentiator. These findings underscore the necessity of moving beyond academic remediation toward a developmental approach to mental health that accounts for regional stressors and the erosion of traditional social buffers.